2003
DOI: 10.18705/1607-419x-2003-9-5-160-163
|View full text |Cite
|
Sign up to set email alerts
|

Inpact of bisoprolol therapy on brain perfusion in patients with metabolic syndrome

Abstract: In the metabolic syndrome, the main cause of death is cardiovascular events due to the high rate of damage to target organs, lb treat patients with the metabolic syndrome, it is necessary to more thoroughly choose drugs or their combination to prevent adverse metabolic effects and at the same time to adequately monitor blood pressure. It has been long considered that β-blockers exert a negative effect on lipid and carbohydrate metabolism and they arc able to deteriorate brain perfusion in patients with arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…Additional factors contributing to microvascular brain lesions in MetS may be autonomic neuropathy and endothelial dysfunction . Researcher studying cerebral perfusion considered abnormal cerebrovascular autoregulation as one of the pathogenic mechanisms of neurocognitive dysfunction in the presence of high blood pressure . The results of our study suggested that reduced cerebral perfusion is one of the major causes of neurocognitive deficit in patients with MetS and is closely associated with the circadian blood pressure profile.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Additional factors contributing to microvascular brain lesions in MetS may be autonomic neuropathy and endothelial dysfunction . Researcher studying cerebral perfusion considered abnormal cerebrovascular autoregulation as one of the pathogenic mechanisms of neurocognitive dysfunction in the presence of high blood pressure . The results of our study suggested that reduced cerebral perfusion is one of the major causes of neurocognitive deficit in patients with MetS and is closely associated with the circadian blood pressure profile.…”
Section: Discussionmentioning
confidence: 54%
“…Separate components of the metabolic syndrome can exert negative impact on cerebral perfusion and, consequently, on cognitive function. For instance, arterial hypertension , dyslipidemia , and hyperinsulinemia increase the risk of dementia and cognitive impairment. Moreover, patients with MetS are prone to thrombogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Причем нейтральность влияния на метаболизм глюкозы не изменялась при использовании доз 5 и 10 мг бисопролола даже у пациентов с сахарным диабетом [19]. Уровень инсулина и показатели чувствительности тканей к инсулину достоверно не менялись при назначении оригинального бисопролола пациентам с метаболическим синдромом [20]. Таким образом, отсутствие неблагоприятных эффектов на толерантность к глюкозе и чувствительность к инсулину бисопролола связаны с высокой степенью селективности к β1-адренорецепторам, что отличает препарат среди других БАБ [21].…”
Section: представители бета-адреноблокаторов в клинической практикеunclassified
“…Причем достоверных изменений общего холестерина, его фракций и триглицеридов не было выявлено в дозозависимых исследованиях с применением бисопролола в дозах 5-20 мг как в краткосрочных РКИ [24], так и при длительном применении (более 1 года) у больных с АГ [25], что подтвердило нейтральность препарата. В-третьих, в небольшом исследовании у больных с метаболическим синдромом не было выявлено ухудшения мозгового кровообращения на фоне терапии бисопрололом [20].…”
Section: литератураunclassified